2017
DOI: 10.1002/ejp.1036
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment insecurity is positively associated with medically unexplained chronic pain

Abstract: Consistent with earlier research regarding transient physical symptoms, medically unexplained chronic pain was associated with attachment insecurity. Understanding the mechanisms responsible for this association could guide treatment innovations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
(48 reference statements)
4
17
0
Order By: Relevance
“…Furthermore, the findings can be explained through the response patterns of individuals with avoidant attachment, who may tend to underreport symptoms of psychopathology (Mikulincer & Shaver, ), or unpleasant and negative emotions (Garrison, Kahn, Sauer, & Florczak, ). The current findings are in line with the research showing that avoidant individuals report physical symptoms more frequently suggesting their tendency to experience psychological distress in the form of physical complaints (McWilliams, ). Thus, avoidant individuals may tend to deny depression and anxiety items on DASS but may be more forthcoming while disclosing stress‐related items which tap into more physiological aspects of distress (e.g., nervous arousal, difficulty relaxing, over‐reactivity).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the findings can be explained through the response patterns of individuals with avoidant attachment, who may tend to underreport symptoms of psychopathology (Mikulincer & Shaver, ), or unpleasant and negative emotions (Garrison, Kahn, Sauer, & Florczak, ). The current findings are in line with the research showing that avoidant individuals report physical symptoms more frequently suggesting their tendency to experience psychological distress in the form of physical complaints (McWilliams, ). Thus, avoidant individuals may tend to deny depression and anxiety items on DASS but may be more forthcoming while disclosing stress‐related items which tap into more physiological aspects of distress (e.g., nervous arousal, difficulty relaxing, over‐reactivity).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Gil et al [31] reported positive associations between ambivalent attachment styles, parental bonding, and alexithymia among patients with somatoform disorders. Particularly, with regard to chronic pain patients, many studies have investigated the relationship between attachment style and chronic pain [32][33][34] as well as parental bonding and chronic pain [35]. The findings suggest that insecure attachment and inadequate parental care are significantly associated with chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Anno et al (Anno et al 2015) showed that in a general adult populationt the prevalence of chronic pain was higher in individuals reporting affectionless parental bonding style in childhood. Mc Williams et al (McWilliams 2017) found that even after adjusting for depressive and anxiety disorders attachment insecurity was positively associated with medically unexplained chronic pain.…”
Section: Introductionmentioning
confidence: 99%